Knowledge, Attitude and Awareness on Status of Administering Intramuscular Injection Among Dental Students - CHANDRASEKHAR, HARSHINEE; GANAPATHY, DHANRAJ; PANDURANGAN, KIRAN KUMAR; VELAYUDHAN, ASHOK (The journal of contemporary issues in business and government, 2020)
Intramuscular Injections are given directly to the muscles as they are rich in blood supply and medications are absorbed faster. The common sites for IM injection include Deltoid, dorsogluteal, rectus femoris, vastus lateralis and ventrogluteal. Larger amount of medication can be given through the IM route compared to other routes of administration. Medications like Atropine, Naloxone, Ketamine, Penicillin, Diazepam, Hepatitis vaccine, Rabies vaccine, Influenza vaccines are administered through intramuscular routes. It is important to know about IM injections as improper administration of medications can cause various complications. Some of the complications include Tissue necrosis, Abscess and Nerve injuries.The Aim of the study is to determine regarding the usage of intramuscular injections and to create awareness among dental students on administration of IM injections. Majority of the dental students within the study were aware of the term intramuscular injections.